Baekdudnegan the great Baekdu meridian [videorecording] - Kim, Ki-Dong.; Jung, Hyung Gun.; On, Seung-In. (s.l. Arirang TV)
A journey to the mountain range from Mount Chin, Mount Dukyu, Mount Taebaek, Mount Odoe and Mount Surak. A look at the traditional tea house and the buddhist ritual.
VHS.
CREDITS: Director of photography, Jong-Chan Park, Yeun-Koo Kim ; Editor, Duk-il Kim ; Narrator, Michael Irwin.
Keywords: Mountains -- Korea; Rites and rituals -- Korea; Korea -- Description and travel; Korea -- Social life and customs